Mexico : Financial Sector Assessment Program Update; Detailed Assessment of Compliance with the Basel Core Principles for Effective Banking Supervision and Transparency of Banking Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper presents a Detailed Assessment of Mexico's compliance with the Basel Core Principles for Effective Banking Supervision and Transparency of Banking Supervision. Fiscal consolidation reduced the gross public debt-to-GDP ratio to below 50 percent, providing the foundations for a monetary policy able to bring inflation down to less than 4 percent, in the context of a floating exchange rate. These improvements have contributed to Mexico's achievement of investment-grade rating, uninterrupted access to capital at low cost, and resilience to shocks, such as the Russian crisis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet